Propriedades ópticas, eletrônicase estruturaisde monocamadas híbridas - Pontes, Jessé Medeiros (2023)
Nanoscale materials composed of carbon, boron and nitrogen atoms have unique properties and can be useful in the development of new technologies. In this thesis, we present two studies, where we use first-principle calculations based on the density functional theory formalism, as implemented in the SIESTA code, to describe structural, electronic and optical properties of nanomaterials composed of carbon, boron and nitrogen. The first work deals with the influence of substitutional defects on the optical, electronic and structural properties of PhaCBN monolayers. Specifically, we investigated the electronic, optical and structural properties of various structures known as PhaCBN. We found that some of these structures are stable, as they have positive phonon frequencies and low formation energies. We also showed that the electronic structure of PhaCBNs presented a semiconductor behavior, with an energy bandgap ranging from 0.33 eV to 2.41 eV. In addition, we found in the results for optical absorption that some structures have absorption peaks in the visible region and very low levels of reflectivity. This work suggests that PhaCBN monolayers are promising materials for applications in electronic and optoelectronic devices. In the second work, we investigated the structural, electronic and optical properties of the PAI-BN monolayer. This structure is composed of pentagonal, hexagonal and heptagonal rings, much like PhaCBN. We found that this structure presents dynamic and thermal stability and its energy is slightly higher than that obtained for the hexagonal monolayer of boron nitride (h-BN). Our calculations for the electronic structure showed that the PAI-BN presents a bandgap of 2.50 eV, which is approximately half of the h-BN bandgap, thus presenting a semiconductor behavior. Furthermore, we verified, based on optical absorption results, that PAI-BN is transparent in the infrared and visible regions, absorbing only in the ultraviolet region. Therefore, based on these results, we can also consider the possibility of applications of this nanostructure in electronic and optoelectronic devices.